Pengaruh Penggunaan Aplikasi Al-Qur’an Android Terhadap Motivasi Membaca Al-Qur’an Pada Siswa Smp Islam Terpadu Al-Falah Muhammadiyah Cilawu Garut - Amalia , Debby Rizki; Vatimah, Vini Sri; Abdullah, Deba Muslim (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
Reading the Qur'an is crucial to prevent humanity from going astray in life. To comprehend the content and meaning of any text, one must first read it; this holds true for the Qur'an as well. Motivation is a key factor that encourages Muslims to regularly read the Qur'an. In the digital era, the Qur'an Android app has become a significant tool for encouraging teenagers to engage in Qur'anic reading. This study aims to describe: (1) The impact of using the Qur'an Android app on the motivation to read the Qur'an among teenagers at SMP IT Al-Falah Cilawu. (2) The level of motivation for reading the Qur'an among teenagers at SMP IT Al-Falah Cilawu. (3) The effect of the Qur'an Android app on the reading motivation of teenagers at SMP IT Al-Falah. Consequently, this study seeks to understand the relationship between the use of the Qur'an Android app (Variable X) and the motivation to read the Qur'an among teenagers (Variable Y). The research employs an inferential quantitative method, gathering data and information about the phenomena under study. Data collection techniques include questionnaires distributed to 27 respondents, observations, and document studies. Data analysis is conducted using statistical data analysis methods. The statistical test results indicate that the use of the Qur'an Android app influences reading motivation among students at SMP IT Al-Falah Muhammadiyah Cilawu Garut by 33.55%. The hypothesis test results show that the impact of using the Qur'an Android app on the reading motivation of 9th-grade students at SMP IT Al-Falah Cilawu is 43.5%, while the remaining 56.45% is influenced by other factors not covered in this study. Keywords: Qur'an Android App, Reading Motivation, Impact on Students at SMP IT Al-Falah Muhammadiyah Cilawu Garut